2020
DOI: 10.1111/1467-8551.12417
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Marketization in Public Healthcare Systems: Performing Reform in the English National Health Service

Abstract: To implement marketization in public healthcare systems, policymakers need to situate abstract models of prescriptive practice in complex user settings. Using a performativity lens, we show how policy processes attempt to bring about the changes they presume. Investigating the implementation of the Health and Social Care Act 2012, and the development of policy instruments and 'Clinical Commissioning Groups', we explicate the performance of a marketization programme. Our longitudinal study of the interactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…For example, Mason and Araujo (2020) illustrate how the performative struggles of a policy model produced multiple reformulations in the English National Health System. These reconceptualizations were distributed across a multitude of actors at different scales and relied on the 'cobbling together' of various elements of theories through a process of trial and error.…”
Section: Performing Ambiguous Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mason and Araujo (2020) illustrate how the performative struggles of a policy model produced multiple reformulations in the English National Health System. These reconceptualizations were distributed across a multitude of actors at different scales and relied on the 'cobbling together' of various elements of theories through a process of trial and error.…”
Section: Performing Ambiguous Conceptsmentioning
confidence: 99%
“…Scholars interested in performativity have demonstrated that enactments of conceptual ideas can contribute to shaping organizational orders (e.g. Beunza & Ferraro, 2019; D’Adderio & Pollock, 2014; Mason & Araujo, 2020). While performativity studies often assume an inherent precision in the concepts or theories that perform, some scholars have pointed out that even the purest theoretical forms require careful ‘market work’ (Cochoy & Dubuisson-Quellier, 2013) to become contextualized in practice (Cabantous, Gond, & Johnson-Cramer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies on how health policies influence the development of healthcare markets (cf. Mason & Araujo, 2021), or how media systems play a role in food markets (cf. Hopkinson, 2017), made inroads in this domain, but few studies have attempted to capture the multiple systems that construct and perform markets.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of expertise and materials at hand is an important one for those seeking to understand and intervene in markets (Mason & Araujo, 2021). What is at hand, in our market research illustration, is knowledge of methods, tools and techniques.…”
Section: Market Infrastructuringmentioning
confidence: 99%
“…The existing public management scholarship explores different and at times competing high‐level models: including, Traditional Public Administration (TPA), the New Public Management (NPM) (Hansen and Jacobsen, 2016; Mason and Araujo, 2021), Network Governance (NG) (Osborne, 2010) and now PV (Moore, 1995) as a possible post‐NPM model (Talbot, 2009; Bryson, Crosby and Bloomberg, 2014).…”
Section: Alternative Public Management Modelsmentioning
confidence: 99%